Study of renal functions in metabolic syndrome and its correlation with various parameters - N., Anand; A., Vidya T. (International Journal of Research in Medical Sciences, 2020)
Background: Metabolic syndrome includes a constellation of various metabolic abnormalities that have been associated with cardiovascular disease, stroke and all-cause mortality in the general population. It has now been established that it is also associated with renal dysfunction. This study was done to assess renal function in metabolic syndrome in Indian population as well as its correlation with different parameters of the metabolic syndrome. Methods: A cross-sectional study was conducted in a university hospital from 2014 - 2015. Renal functions were studied in 100 obese individuals, 50 with and 50 without metabolic syndrome after informed consent and the results were analysed. Results: 100 obese individuals, 50 with and 50 without metabolic syndrome were compared. All underwent a physical examination and relevant investigations. All parameters of renal function showed significant derangement in cases as compared to controls. 38 patients (76%) among the cases (N=50) of metabolic syndrome had altered renal functions versus 9 patients (18%) among controls (n=50). Individually, there was a significant correlation of altered renal function (reduced estimated glomerular filtration rate eGFR and presence of microalbuminuria) with fasting blood glucose and systolic blood pressure (p=0.001), diastolic pressure (p=0.003) and triglyceride levels (p=0.036). High density lipoprotein-cholesterol levels did not show a significant correlation. Conclusions: Obese individuals with metabolic syndrome have significant derangement of renal functions as compared to those without metabolic syndrome. Most parameters of the syndrome are also independently associated with alteration of renal functions.